Stress events and stress symptoms in Chinese secondary school students: gender and academic year characteristics of the relationship - Ma, Aimin; Tan, Shuying; Chen, Jin; Lou, Hu (Frontiers in Public Health, 2024)
Objective To explore the relationship between stress events and stress symptoms and their gender and academic year characteristics in Chinese secondary school students. Methods 4,995 secondary school students were investigated by the Adolescent Self-rating Life Events Checklist (ASLEC) and the Calgary Symptoms of Stress Inventory (C-SOSI). Results First, there were significant differences in all dimensions and total scores of stress events and stress symptoms between boys and girls in secondary school and between junior high school students and senior high school students. Second, the dimensions and total scores of stress events in secondary school students are positively correlated with the dimensions and total scores of stress symptoms. Third, the influence of punishment on the stress symptoms of secondary school boys is the most obvious, and the influence of punishment, adaption, relationship stress, and learning stress on the stress symptoms of secondary school girls is the most obvious. The influence of punishment on the stress symptoms of junior high school students is the most obvious, and the influence of punishment and relationship on the stress symptoms of senior high school students is the most obvious. Conclusion Stress events and stress symptoms of Chinese secondary school students have significant differences in gender and academic year. The same stress event has different influence mechanisms on the stress symptoms of Chinese secondary school students of different genders and different academic years.